PENGARUH PERSEPSI TEKNOLOGI INFORMASI, RISIKO DAN HANDLING OF COMPLAINTS TERHADAP MINAT NASABAH DALAM MENGGUNAKAN INTERNET BANKING (STUDI KASUS BPRS BAKTI SUMEKAR CABANG PRAGAAN) - Matnin; Kunaifi, Aang; Ubaidillah, Ach (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
In using internet banking, there is convenience to access and easy operating procedures make customers feel comfortable using internet banking and reduce the risks that occur when making transactions directly to banks, making customers think about switching to using internet technology advances to carry out both transactions and just see the rest. balance held. Ease of use is a person's level of belief that using a particular system does not require a lot of effort. Although the effort according to each person is different but in general to avoid rejection from users of the developed system, the system must be easy to apply by users without spending heavy effort. Based on the results of research on the influence of perceptions of information technology, risk and handling of complaints, it can be concluded that: first, the effect of the variable perception of information technology on customer interest in using internet banking, shows a positive and significant influence partially. Second, the effect of the risk variable on customer interest in using internet banking, shows a negative and partially insignificant effect. Third, the effect of handling of complaints on customer interest in using internet banking, shows that there is a positive and significant influence partially. Fourth, the influence of perceptions of information technology, risk and handling of risk complaints on customer interest in using internet banking, together (simultaneously) shows a positive and significant influence.